Kecerdasan Emosional, Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Mooij Di Kota Denpasar - Anak Agung Sagung Dara Triana; Ida Bagus Gde Agung Yoga Pramana (Universitas Veteran Bangun Nusantara, 2025)
This research aims to examine the effect of emotional intelligence, communication, and the work environment on employee performance at Mooij, located in Denpasar City. The study employs a quantitative approach using a survey method, with a saturated sample consisting of 100 employees. Data were obtained through questionnaires and analyzed using multiple linear regression analysis, along with t-tests, F-tests, and the coefficient of determination. The findings reveal that emotional intelligence has a negative and significant influence on employee performance (B = –0.223; Sig. = 0.019), while communication demonstrates a positive and significant effect (B = 0.228; Sig. = 0.042). In contrast, the work environment is found to have a negative and significant effect on employee performance (B = –0.229; Sig. = 0.019). Simultaneously, emotional intelligence, communication, and the work environment collectively have a significant impact on employee performance, as indicated by an F-value of 4.001 and a significance level of 0.019, with these variables accounting for 75.6% of the variance in employee performance. These results emphasize the critical role of effective communication and appropriate work environment management in improving employee performance. Additionally, the development of emotional intelligence should be carefully managed to prevent potential declines in performance. The study offers practical insights for Mooij’s management in formulating human resource strategies aimed at enhancing employee performance.